Tilted magnetic field and spin interactions on a two-dimensional electron gas at low temperatures - Gammag, Rayda P. (2011)
Experiments on a two-dimensional electron gas (2DEG) under an inversion asymmetric quantum well reveal spin splitting even in the absence of an applied magnetic field. The splitting is caused by an induced magnetic field resulting from the coupling of an electron?s momentum with the potential gradient. The associated potential energy is called the Rashba spin-orbit interaction (RSOI). In this work we investigate the interplay of the direction of B with RSOI and Zeeman interactions. We invoke that crossing levels have equal probability. This allows us to obtain the eigenvalues exactly. To the best of our knowledge this is the first time an exact solution is acquired for tilted magnetic fields. From the eigenvalues obtained, we notice that the crossing are removed upon tilting. They are, however recovered at large tilt angles. The emergence of the crossings is accompanied by beating patterns in the density of states. PACS: 71.70.Ej (Spin-orbit coupling), 71.70.Di (Landau levels), 73.20.At (Electron density of states)